INFLUENCE OF IMPLEMENTING INDEPENDENT CURRICULUM ON THE RELIGIOUS DEVELOPMENT OF JUNIOR HIGH SCHOOLS STUDENT IN MAKASSAR CITY - Sandi Pratama; Pertiwi Nurani (Fakultas Tarbiyah, Universitas Ibrahimy, 2024)
The implementation of Merdeka Curriculum in Junior High Schools (SMP) in Makassar City not only aims to improve students' academic achievement, but also to strengthen moral and spiritual values. Religious development is one of the important aspects of this curriculum, which is expected to shape students' characters to be better and noble. This research was conducted to find out how the Merdeka Curriculum affects the religious development patterns of junior high school students in Makassar City. This research uses a survey method with a quantitative approach. The quantitative approach aims to test certain theories by examining the relationship between the variables studied. These variables are measured using research instruments, so that the data obtained are numbers which can then be analyzed using statistical procedures. The sample in this study amounted to 30 junior high school teachers in Makassar City who were randomly selected through the random sampling method. Data collection was carried out by distributing questionnaires (questionnaires) to respondents and conducting documentation. The results showed that the significant value obtained was 0.002, which is smaller than alpha 0.05. This indicates that there is a significant influence between Merdeka Curriculum (X) and religious guidance (Y) of students in Makassar City Junior High School. This test is reinforced by the Fcount result of 11.56, while the Ftable value for n: 30 is 2.27. Because the Fcount value is greater than Ftable (11.56> 2.27), it can be concluded that the Merdeka Curriculum has a significant influence on students' religious development.